2017
DOI: 10.1175/jpo-d-15-0247.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamics of the Southern Senegal Upwelling Center: Observed Variability from Synoptic to Superinertial Scales

Abstract: sources of mixing play a major role in the overall system dynamics through their impact upon the general shelf thermohaline structure, in particular in the vicinity of the upwelling zone. Systematic alongshore variability in thermohaline properties highlight important limitations of the 2D idealization framework that is frequently used in coastal upwelling studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 73 publications
7
78
0
Order By: Relevance
“…Note though that shelf surface waters are, on average, ∼ 1°C too warm in the model (supporting information Text S2). Because a bias of similar amplitude also seems to affect bottom waters over the outer and midshelf (by comparing the simulation with observations from the UPSEN2/ECOAO experiments) [see Capet et al [, Figure 5], we suspect that the model deficiency arises from a lack of offshore isopycnal tilt resulting in the 15°C isotherm being ∼ 20 m too deep at the shelf break. This type of bias is common in upwelling simulations [ Capet et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Note though that shelf surface waters are, on average, ∼ 1°C too warm in the model (supporting information Text S2). Because a bias of similar amplitude also seems to affect bottom waters over the outer and midshelf (by comparing the simulation with observations from the UPSEN2/ECOAO experiments) [see Capet et al [, Figure 5], we suspect that the model deficiency arises from a lack of offshore isopycnal tilt resulting in the 15°C isotherm being ∼ 20 m too deep at the shelf break. This type of bias is common in upwelling simulations [ Capet et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…These observed differences might be due to their physiological characteristics which are relatively distinct: S. aurita is more sensitive to temperature and salinity fluctuation than S. maderensis , which tolerate higher change in salinity and temperature (Ba et al., ; Cury & Fontana, ). This is also explained by the fact that, even if both species occupy the same area in Senegal (Cury & Fontana, ), their relative abundance strongly differs between Northern Senegal (in connection with Mauritania) and Southern Senegal (Capet et al., ; Ndoye et al., ), warmer and less sensitive to the detrimental effects of a strong upwelling season.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this survey, usual upwelling (northerly) winds of 10-15 knots were blowing over the area (Ndoye et al, 2014). Winds weakened just before the survey started ( Figure 2) and blew gently from 7 to 10 March alternating from weak northeasterlies (NE) in the morning to northwesterlies (NW) in the evening (not shown), a usual pattern for this region strongly affected by thermal winds (see Figure 2e in Capet et al, 2017, for the similar diurnal cycle observed in 2013). The relaxation became more pronounced between 10 and 13 March with very weak NW winds punctuated by short periods of weak southerlies.…”
Section: Resultsmentioning
confidence: 93%
“…High-resolution sampling of the water column during UPSEN revealed a short episode of complete subsurface anoxia. Reaching the O2 levels observed at six stations situated within 1-km distance requires the consumption of~60 μmol/kg of oxygen, this value being approximately the background concentration for near-bottom upwelling waters over the southern Senegalese shelf (see Figure 4 in Capet et al, 2017). Ignoring processes other than local phytoplankton degradation and assuming a photosynthesis/respiration reaction with a typical mean carbon:chlorophyll ratio of 50, such reduction requires 10 mgChl-a/m 3 .…”
Section: Discussionmentioning
confidence: 97%